Improved Forehand and Backhand Tennis Court Learning Outcomes by Using Motion Recording and Audio-Visual Image Media - Zulrafli Zulrafli; Kamarudin Kamarudin; Rices Jatra (Universitas PGRI Palembang, 2023)
The research aims to improve the learning process of basic techniques of Forehand and Backhand tennis courts of students by using movement recording devices and Audio Visual Image Media.Â PTK research which is an action research that is carried out cyclically in order to solve problems until the problem is solved. The research subjects of Physical Education and Health Students totaled 32 people. While the object of research is the basic technique process of Forehand and Backhand to solve the problem of completeness of learning court tennis. The results showed that in the first cycle only 35% of students in the complete category. In cycle II, there was an increase in students who reached 87.5% completeness. therefore the hypothesis of action is acceptable, namely that there is an increase after recording movements and Audio Visual Media in the learning process